The Influence Factors of Going Concern Audit Opinion Acceptance Using Firm Size as A Moderating Variable - Fitra Hakiki; Ratna Mappanyukki (Journal of Social Science, 2022)
A phenomenon this research linked to the mistake from auditor when giving audits opinions, therefore this research aimed to discover factors the receipt of going concern audit opinion with the firm size as a moderating variable and factors including independent commissioners, audit committee, and financial distress. Furthermore, the logistic analysis regression with the Eviews program was the hypothesis test used. The results of this study, the audit committee and financial distress had a notable effect towards going concern audit opinion, while independent commissioners had no impact. Firm size moderates the effect of the audit committee & financial distress on the opinion acceptance. However, it did not moderate the independent commissioners towards going concern opinion. Therefore, the results are useful for creditors and investors as a consideration before investing in the mining industry by assessing the company's financial condition related to its ability to continue going concern.